2020
DOI: 10.1016/j.ijsu.2020.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection in Cirrhotic liver: Are there any limits?

Abstract: Liver resection remains one of the most technically challenging surgical procedure in abdominal surgery due to the complex anatomical arrangement in the liver and its rich blood supply that constitutes about 20% of the cardiac output per cycle. The challenge for resection in cirrhotic livers is even higher because of the impact of surgical stress and trauma imposed on borderline liver function and the impaired ability for liver regeneration in cirrhotic livers. Nonetheless, evolution and advancement in surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…Generally, patients with cirrhosis have a poorer hepatic function and are prone to have higher short-term postoperative mortality and morbidity than noncirrhotic patients. [7][8][9] Existing studies have indicated that cirrhotic liver results in a higher risk of hepatectomy liver failure due to insufficient functional liver remnant remains for maintaining postoperatively normal physiological functions. [9][10][11] Radical surgical resection is believed to be the only potentially curative management for patients with ICC, while a lower chance of receiving radical resection means Note: "N1-3″ indicated the patients underwent surgery and the number of LND in the range of 1-3, "N4 + " indicated the patients underwent surgery and the number of LND in the range of >4; PSM: propensity score matching.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, patients with cirrhosis have a poorer hepatic function and are prone to have higher short-term postoperative mortality and morbidity than noncirrhotic patients. [7][8][9] Existing studies have indicated that cirrhotic liver results in a higher risk of hepatectomy liver failure due to insufficient functional liver remnant remains for maintaining postoperatively normal physiological functions. [9][10][11] Radical surgical resection is believed to be the only potentially curative management for patients with ICC, while a lower chance of receiving radical resection means Note: "N1-3″ indicated the patients underwent surgery and the number of LND in the range of 1-3, "N4 + " indicated the patients underwent surgery and the number of LND in the range of >4; PSM: propensity score matching.…”
Section: Resultsmentioning
confidence: 99%
“…Like HCC, cirrhosis was observed in the majority (62.5%) of CHC patients with known Metavir stage. The liver reserve function determines the choice of treatment to a great extent, and cirrhosis has been a well-recognized risk factor of postoperative liver failure, leading to poor outcomes for CHC patients (SHR = 2.004, 95% CI = 1.145–3.510, P =0.015) [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver has a remarkable potential for regeneration, this regenerative capacity becomes impaired with serious liver fibrosis. ( 16 ) The transition of quiescent HSCs to activated, scar‐forming, myofibroblast‐like cells leads to excessive extracellular matrix synthesis. ( 17 , 18 ) This abnormal scar formation in the liver has been shown to hold back hepatocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%